Analisis Pendapatan Pedagang Sebelum dan Selama Adanya Pandemi Covid-19 (Studi Kasus di Pasar Tradisional Sungai Andai, Kecamatan Banjarmasin Utara) - Lambradi, Anggraini; Suherty, Lina (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This research was conducted (1) to find out whether there were differences in the income of traders before and during the Covid-19 pandemic at the Sungai Andai Traditional Market, North Banjarmasin District. (2 To find out what strategies are being used by traders to increase income during the Covid-19 pandemic at the Sungai Andai Traditional Market, North Banjarmasin District.This type of research is descriptive quantitative research, while the analysis technique used is paired t-test using SPSS. The results of this study show that there is a significant difference between the income of traders before Covid 19 and the income of traders during Covid 19, where most of the traders experienced a decrease in their income from doing business such as giving discounts or sales and some using social media to increase their income during the pandemic.